(untitled) (Ustozlar uchun, 2026)
This article analyzes the evolution of gender roles in the modern world, their historical formation, and their contemporary transformation from a scientific and theoretical perspective. It highlights how the traditional social roles associated with men and women have significantly changed under the influence of globalization, industrialization, educational reforms, the development of information and communication technologies, and feminist movements. The article broadly examines issues such as gender equality, equal opportunities, participation in the labor market, the transformation of family roles, and the increasing activity of women in socio-political life.The study also analyzes the role of economic independence and education in the transformation of gender roles, emphasizing that women’s growing participation in social, political, and economic life has expanded their opportunities for education, professional development, and a worthy place in the labor market. It also discusses the growing tendency in modern families toward equal distribution of responsibilities in household management and child-rearing, which strengthens partnership-based family relations.The article emphasizes the decline of gender stereotypes and the importance of evaluating an individual’s social role not by gender, but according to personal abilities, potential, and interests. In addition, it demonstrates the significance of implementing gender equality principles in governance and leadership for ensuring management efficiency, social justice, and sustainable development.